Significant photoelectrochemical enhancement of TiO2 photoanodes from Ni(OH)2 electrocatalyst overcoating. (1st December 2017) - Li, Hongxia; Jiang, Liyun; Xi, Junhua; Mu, Jinxia; Wu, Xin
Abstract: Introducing electrocatalysts onto the surface of photoanodes is a common way to improve photoelectrochemical (PEC) activity of photoanodes. In this paper, we report a simple and effective approach to load Ni(OH)2 electrocatalyst nanosheets on TiO2 surface via electrochemical deposition. The results indicated that deposition of Ni(OH)2 on TiO2 photoelectrode could remarkably promote the PEC activity by suppressing electron–hole recombination under AM1.5G illumination. The effects of OH − concentration in the electrolyte and coating thickness of Ni(OH)2 layer were investigated. As a result, we find that electrocatalytic effect of Ni(OH)2 with appropriate amount increased monotonically in alkaline solution, while excessive Ni(OH)2 electrocatalyst could reduce the photocatalytic effect by limiting the light absorption. The result demonstrates a new route for improving the performance of photoanode for oxygen evolution reaction.